Hands-On Enterprise Automation with Python Automate common administrative and security tasks with Python - Aly, Bassem (Packt Publishing Limited, 2018)
bInvent your own Python scripts to automate your infrastructure/bh2About This Book/h2ulliMake the most of Python libraries and modules to automate your infrastructure/liliLeverage Python programming to automate server configurations and administration tasks/liliEfficiently develop your Python skill set/li/ulh2Who This Book Is For/h2Hands-On Enterprise Automation with Python is for system administrators and DevOps engineers who are looking for an alternative to major automation frameworks such as Puppet and Chef.